Characterization of Firebrands Released From Different Burning Tree Species - Almeida, Miguel; Porto, Leonardo; Viegas, Domingos (Frontiers in Mechanical Engineering, 2021)
The number, dimensions, and initial velocity of the firebrands released from burning Quercus suber, Eucalyptus globulus, Quercus robur, and Pinus pinaster trees were analyzed in laboratory experiments using a particle image velocimetry system. Additionally, the flame height, tree mass decay, vertical flow velocity, and temperature at the top of the trees were measured during the experiments. The relationship between the various parameters was analyzed and a good connection was found. The specimens burnt were mostly young trees, so large particles (e.g., pine cones, thick trunk barks, branches) were not included in this study as they were not present. Actually, the firebrands produced in the laboratory tests, mainly burning leaves, had a cross-sectional area of <1,600 mm2, having the potential to cause short distance spotting (up to tens of meters). Quercus trees are often considered to have a lower fire risk than eucalyptus or pine trees. However, in this study, Quercus suber and Quercus robur were the species that produced more firebrands, both in terms of number and total volume. The tests with Quercus suber were the only ones using specimens from an adult tree, confirming the great importance of the age of trees in the propensity to release firebrands. The results obtained with Quercus robur confirmed the high tendency of this species to originate spot fires at a short distance. Thus, these results are of great relevance to afforestation plans and to evaluating the risk of the presence of these species in wildland–urban interface areas.